Does the difference in valuation between domestic and foreign investors help explain their distinct holdings of domestic stocks? - Kang, Hyung Cheol; Lee, Dong Wook; Park, Kyung Suh (Journal of Banking & Finance, 2010)
This paper proposes an investor heterogeneity approach to the different domestic stock holdings between domestic and foreign investors. Specifically, we hypothesize that domestic and foreign investors evaluate domestic stocks via different models and thus arrive at different valuations for them; consequently, the two investor groups are attracted to different sets of domestic stocks. Using panel data from Korea, we find strong support for our hypothesis. More precisely, we find that the foreign ownership of a stock increases with foreigners’ valuation for the stock in excess of that of domestic investors. As we control for various firm characteristics known to be correlated with foreign ownership, our results indicate that the valuation difference between domestic and foreign investors can help explain the allocation of domestic stocks between the two groups over and above the existing explanations.